Aplikasi VSD Inverter Dalam Penghematan Konversi Energi - Indra Kusuma (Institut Sains dan Teknologi Nasional, 2016)
AHSRAE Indonesia Chapter Seminar 2016 always improve the systems and implementation for efficiency energy actually the method and the technical, Chillers plant efficiency with the Green Chiller Concept. In general, as the Building Manager (Management Building) has a target of quality management on Energy (ISO 50001), such as Cost Effective and Saving Energy on the use and maintenance of the units Equipment available on, especially those closely related to the mechanical and electrical components of control , The use and regular maintenance is essential in the mechanical and electrical components where it is very related to the work function of equipment (Unit Equipment) such support; Air Conditioning Engineering (AHU / HVAC / Chiller), Heater (Steam Boiler), Pumps Hydrant and Water (WTP). That on the part of this equipment is widely available induction motor (3 phase) as well as the need of electric power consumption is very frequent and quite large when the engine start switch, due to the Inrust current (6x fold) when the machine Turned ON.Inverters or Variable Speed Drive (VSD) is an electronic device that functions as a controller rounds induction motor 3 phase in Variable star-stop (Soft Start, Smooth, Stage) that the inverter can be in Settings (adjustable) drive the rotation Fan or AC Induction Motor 3 phase in Air flow requirements to transfer flow (CFM) on the unit for the purpose of cooling machine efficiency